Examining the relationship between ultra-processed food consumption and quality of life among middle school students - Eynallı, Onur; Demirkol, Mehmet Emin; Tamam, Lut; Demirtaş, Sinem Çetin; Yeşiloğlu, Caner (Journal of Dependence, 2026)
Objective: With advancing technology and urbanization, traditional dietary habits are increasingly being replaced by ultra-processed foods (UPFs), which are practical, energy-dense, and low in nutritional value. Concerns have arisen that UPF consumption may adversely affect both physical and mental health in young people.This study aimed to examine the relationships between UPF consumption, quality of life, psychological symptoms, and food addiction among middle school students.Methods: This descriptive cross-sectional study included 207 students 10–15 years aged (predominantly 11–14 years) attending schools in the Yüreğir district of Adana, Türkiye. Data were collected using a Sociodemographic Information Form, the Food Frequency Questionnaire (FFQ), the Yale Food Addiction Scale (YFAS), KIDSCREEN-52, and the Revised Child Anxiety and Depression Scale – Youth Version (RCADS-Y). Statistical analyses were conducted using SPSS 26.Results: Overall, 46.9% of students met the YFAS diagnostic criteria for food addiction (≥3 symptoms plus clinically significant impairment/distress). UPF consumption frequency was negatively correlated with multiple health-related quality-of-life domains, including Physical Well-being (r = −0.45, p < 0.001), Moods & Emotions (r = −0.30, p < 0.001), Friends (r = −0.18, p = 0.012), and School Environment (r = −0.30, p < 0.001), while it was positively correlated with Bullying (r = 0.25, p = 0.001). UPF consumption was positively associated with food addiction (r = 0.424, p = 0.001). Family income level was significantly associated with UPF intake (p = 0.037), with the highest UPF consumption observed among middle-income households. No significant relationship was observed between BMI and food addiction status...